Research on the attenuation characteristics of seismic energy in multicoal seam mining and the warning method of rock burst - Hongwei Mu; Yongliang Zhang; Mingzhong Gao; Quanlin Zhu; Jingbo Li; Jinfeng Cao; Wentao Fan (Energy Science & Engineering)
Abstract The mechanism of rock burst induced by the superposition of dynamic and static loads in multicoal seam mining is unique. To investigate the propagation attenuation law of large‐energy microseismic events and the induced mechanism of rock burst under this condition, this study employs FLAC3D's dynamic module to simulate and analyze the influence of propagation distance, overburden structure in multicoal seam mining, and interlayer plastic zone on vibration wave attenuation. Results indicate that when coal seams are mined at close distances, vibration waves experience significant attenuation while passing through the plastic zone between two layers of coal. At equal attenuation distances, multicoal seam mining structures exhibit greater effects on vibration wave attenuation. Considering differences between rock‐burst induction mechanisms in close‐distance coal seam group mining versus single coal seam mining, a discriminant criterion for rock bursts induced by superimposed dynamic and static loads in multicoal seam mining is established along with a monitoring and early warning method suitable for such conditions.